Revision of the Belostoma triangulum group (Insecta: Heteroptera: Belostomatidae) - Stefanello, Fabiano; Ribeiro, José Ricardo Inacio; Estévez, Ana Lia (Zootaxa, 2021)
The genus Belostoma comprises about 70 species classified in sixteen species groups. Here, the remarkable Belostoma triangulum group sensu Lauck, 1964, is revised. Belostoma bicavum Lauck, 1964 is proposed as a junior synonym of B. bachmanni De Carlo, 1957, which is added to this group. Thus, the rearranged group is now composed of two species: Belostoma bachmanni and B. triangulum Lauck, 1964. Redescriptions of these species are presented including a discussion about comparative morphology with other species of the genus. The geographic distributions of the species in the B. triangulum group are also updated.